Absence of Clinical and Hemodynamic Consequences due to Posterior Tibial Artery Congenital Aplasia. (21st May 2015) - Karaolanis, Georgios; Galyfos, George; Karanikola, Evridiki; Palla, Viktoria Varvara; Filis, Konstantinos
Abstract : The exact knowledge of popliteal artery and its branches' anatomic variations is important for the clinical practice of angiology, vascular surgery, and interventional procedures. Congenital absence of the artery leads, in some cases, to early malformations of the extremity in the childhood; however, it may also remain asymptomatic. We present an unusual case of a 76-year-old male patient complaining of paraesthesia in both limbs and bilateral aplasia of posterior tibial artery (PTA). Physical examination, ankle-brachial indexes, before and after exercise, arterial duplex scan, and magnetic resonance arteriography were performed. Arterial pulses for PTA at the level of the ankle were normal; arterial duplex study showed biphasic arterial flow at the level of the ankle. Color duplex ultrasound as well as magnetic resonance arteriography revealed the absence of the PTA in both limbs. The vascularization of the fibula was bilaterally normal. The patient underwent also neurological examination and electromyography, which were normal. The evaluation of the possible clinical signs and symptoms and the hemodynamic consequences of this condition are further discussed.